Anticipatory postural adjustments associated with arm movement in Parkinson's disease: a biomechanical analysis. Issue 8 (26th November 2007) - Bleuse, S; Cassim, F; Blatt, J-L; Labyt, E; Bourriez, J-L; Derambure, P; Destée, A; Defebvre, L
Abstract : Objective: To study anticipatory postural adjustments (APAs) in Parkinson's disease (PD) via a biomechanical analysis, including vertical torque (Tz). Methods: Ten patients with PD (in the "off-drug" condition) and 10 age matched controls were included. While standing on a force platform, the subject performed a right shoulder flexion in order to grasp a handle in front of him/her, under three conditions (all at maximal velocity): movement triggered by a sound signal and loaded/non-loaded, self-paced movement. The anteroposterior coordinates of the centre of pressure (COP) and Tz were calculated. Results: A group effect was observed for Tz and COP in patients with PD (compared with controls): the maximal velocity peak appeared later and the amplitude of the COP backward displacement and the area of the positive phase of Tz were lower, whereas the duration of the positive phase of Tz was greater. Interaction analysis showed that the area of Tz was especially affected in the triggered condition and the loaded, self-paced condition. The onset of the COP backward displacement was delayed in the triggered condition. Conclusion: Our biomechanical analysis revealed that patients with PD do indeed perform APAs prior to unilateral arm movement, although there were some abnormalities. The reduced APA magnitude appears to correspond to a strategy for not endangering postural balance.